1978
DOI: 10.1039/dt9780000651
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of (η-benzene)tricarbonylchromium, tricarbonyl-(η-cyclopentadienyl)manganese, and (η-cyclobutadiene)- and (tris-methylenemethane)-tricarbonyliron in frozen gas matrices at 12 K. Infrared spectroscopic evidence for dicarbonylmetal and dicarbonyl-(dinitrogen)metai complexes

Abstract: C4H4) (CO) 31 and [Fe(C(CHJ 3HCO) 31 * [711472

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 0 publications
5
30
0
Order By: Relevance
“…4). Further reduction of the excitation wavelength to 334 nm resulted in a significant increase in the formation of (g 6 -C 6 H 6 )Cr(CO) 2 as observed by Rest et al who used broad-band irradiation techniques but the weak feature at 2060 cm À1 is depleted under these conditions [21].…”
Section: Matrix Isolation Experimentsmentioning
confidence: 77%
See 1 more Smart Citation
“…4). Further reduction of the excitation wavelength to 334 nm resulted in a significant increase in the formation of (g 6 -C 6 H 6 )Cr(CO) 2 as observed by Rest et al who used broad-band irradiation techniques but the weak feature at 2060 cm À1 is depleted under these conditions [21].…”
Section: Matrix Isolation Experimentsmentioning
confidence: 77%
“…Low temperature photochemistry of (g 6 -C 6 H 6 )Cr(CO) 3 in a CH 4 matrix at 12 K Despite the previously published work on the photochemistry of (g 6 -C 6 H 6 )Cr(CO) 3 in low temperature matrixes [21], it was decided to revisit this system and to apply the same experimental methodology as applied to the substituted system described later.…”
Section: Matrix Isolation Experimentsmentioning
confidence: 99%
“…The close relationship between time resolved methods and matrix studies is nicely illustrated in the early literature by flash photochemical studies (uv/visible detection) of (C 6 H 6 )Cr(CO) 3 that revealed the presence of a short lived photointermediate [19]. Subsequent studies by Rest established the existence of the CO-loss photoproducts for this compound as well as for CpMn(CO) 3 and (C 4 H 4 )Fe(CO) 3 using inert gas matrices [20]. Braterman and Black had previously observed the CpMn(CO) 3 photoproduct in hydrocarbon glasses [21].…”
Section: Co Loss and Ligand Substitutionmentioning
confidence: 94%
“…This shift in the UV/visible band of Cr(CO) 5 could not be accounted for by matrix environment effects and was interpreted to indicate a significant interaction between the matrix material and the Cr(CO) 5 fragment. Matrix isolation studies have continued to be useful in characterising very unstable reactive fragments in recent years [16], with the interaction of CH 4 with both organometallic complex fragments [17][18][19] and with isolated metal atoms being examined [20].…”
Section: Group VI Metal Carbonyl Alkane Complexesmentioning
confidence: 99%